Predictors of Postdischarge Surgical Recovery Following Laparoscopic Sacrocolpopexy: A Prospective Cohort Study. Issue 5 (May 2020) - Heit, Michael; Carpenter, Janet S.; Chen, Chen X.; Stewart, Ryan; Hamner, Jennifer; Rand, Kevin L.
Abstract : Objectives: Our aim was to identify sociodemographic/clinical, surgical, and psychosocial predictors of postdischarge surgical recovery after laparoscopic sacrocolpopexy. Methods: Study participants (N = 171) with at least stage 2 pelvic organ prolapse completed a preoperative survey measuring hypothesized sociodemographic/clinical, surgical, and psychosocial recovery predictors followed by a postoperative survey at 4 time points (days 7, 14, 42, and 90) that included the Postdischarge Surgical Recovery 13 scale. One multivariate linear regression model was constructed for each time point to regress Postdischarge Surgical Recovery 13 scores on an a priori set of hypothesized predictors. All variables that had P < 0.1 were considered significant predictors of recovery because of the exploratory nature of this study and focus on model building rather than model testing. Results: Predictors of recovery at 1 or more time points included the following: sociodemographic/clinical predictors: older age, higher body mass index, fewer comorbidities, and greater preoperative pain predicted greater recovery; surgical predictors: fewer perioperative complications and greater change in the leading edge of prolapse after surgery predicted greater recovery; psychosocial predictors: less endorsement of doctor's locus of control, greater endorsement of other's locus of control, and less sick role investment predicted greater recovery. Conclusions: Identified sociodemographic/clinical, surgical, and psychosocial predictors should provide physicians with evidence-based guidance on recovery times for patients and family members. This knowledge is critical for informing future research to determine if these predictors are modifiable by changes to our narrative during the preoperative consultation visit. These efforts may reduce the postdischarge surgical recovery for patients with pelvic organ prolapse after laparoscopic sacrocolpopexy, accepting the unique demands on each individual's time. Abstract : Identified sociodemographic/clinical, surgical, and psychosocial predictors provide evidence-based guidance on recovery times for patients and family members.